2022
DOI: 10.1002/slct.202202970
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Heavy Metal by Biosurfactant Producing Novel Halophilic Staphylococcus sciuri subsp. rodentium Strain SE I Isolated from Sambhar Salt Lake

Abstract: The application of halophilic biosurfactant-producing bacteria to remove the pollutants from textile effluent was investigated in the current study. Staphylococcus sciuri subsp. rodentium strain SE I isolated from Sambhar Salt Lake, Rajasthan showed the highest emulsification activity of 65 � 1.2 % after 96 h of incubation with a yield of 0.189 g/l of biosurfactant. The surface tension was reduced to 46.23 mN/m � 0.46 after 72 h at pH 7.0. The presence of non-ribosomal protein sequences gave a hint of the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…subtilis TES IV (MZ683213), C. oceanisediminis TES V (MZ683216), S. sciuri subsp. rodentium strain SE I (MT672499), Bacillus haynesii strain SAII (MT232984), B. licheniformis strain SCI (MT648751), and Bacillus swezeyi strain SE III (MT648773) are surfactin producers (Kumari et al, 2022; Sharma, Gautam, Debnath, & Debnath, 2022; Sharma, Rekhi, & Debnath, 2022; Sharma, Rekhi, Kumari, & Debnath, 2022). R. ruber TES II (MZ683210) is a unique bacterium with potential for surfactin and rhamnolipid production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…subtilis TES IV (MZ683213), C. oceanisediminis TES V (MZ683216), S. sciuri subsp. rodentium strain SE I (MT672499), Bacillus haynesii strain SAII (MT232984), B. licheniformis strain SCI (MT648751), and Bacillus swezeyi strain SE III (MT648773) are surfactin producers (Kumari et al, 2022; Sharma, Gautam, Debnath, & Debnath, 2022; Sharma, Rekhi, & Debnath, 2022; Sharma, Rekhi, Kumari, & Debnath, 2022). R. ruber TES II (MZ683210) is a unique bacterium with potential for surfactin and rhamnolipid production.…”
Section: Resultsmentioning
confidence: 99%
“…subtilis TES IV (MZ683213), Cytobacillus oceanisediminis TES V (MZ683216), Staphylococcus sciuri subsp. rodentium strain SEI (MT672499), Enterobacter cloacae strain AP001 (MK613452), Pseudomonas aeruginosa strain Pa84 (MZ348930.1), Bacillus haynesii strain SAII (MT232984), Bacillus licheniformis strain SCI (MT648751), and Bacillus swezeyi strain SE III (MT648773), isolated from textile effluent contaminated soil and mud from the saline natural estuarine Sambhar lake were selected (Kumari et al, 2022; Sharma, Gautam, Debnath & Debnath et al, 2022; Sharma, Rekhi, & Debnath, 2022; Sharma, Rekhi, Kumari, & Debnath, 2022). All these isolates have been experimentally found to produce biosurfactants and thus are suitable for use as a consortium.…”
Section: Methodsmentioning
confidence: 99%
“…It is evident from previous studies that the consortia demonstrated the potential for producing both rhamnolipid and surfactin types of biosurfactants. 16,17,26 3.5.3. FAME Analysis of the Consortia of Bacteria Using GC-MS. Fatty acid methylated esterification (FAME) was performed for analysis of the fatty acid profile of the biosurfactant from consortia of biosurfactant-producing bacteria using gas chromatography−mass spectrometry (GC-MS).…”
Section: In Silico Analysis Of the Biosurfactant-producingmentioning
confidence: 99%